CERITA BERGAMBAR ‘MEN TIWAS TEKEN MEN SUGIH’ BERBASIS ANDROID - I Gusti Ngurah Putu Reksa Antare; I Ketut Setiawan (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2021)
The development of technology nowadays has gradually scraped the local wisdom which is one of them is folktales. Whereas in folktales contains many positive values about moral, positive character, and ethics in attitude which can be used as learning media especially for children.The lost of folktales can be influenced by the lost of story telling tradition by parents to their children. Moreover, the stories being told orally or contained in the books seem borinh for children because they have been already closed with smartphone which provides many types of entertainments with easier access. Gradually, the folktales which is the inheritance by our ancestors from a long time will be lost. This research aims to create a development of folktales in form of comics based on mobile android by taking a balines story entitled Men Sugih Teken Men Tiwas.Data collection method consists of 3 methods namely interview, observation, and questionnaire with data analysis done in detailed with Human Centered Design method. The comic story entitled Men Sugih Teken Men Tiwas based on mobile android shows a positive result, as alternative media to attract the children’s interest to know about folktales with more modern packaging.